Effect of sulfide on As(III) and As(V) sequestration by ferrihydrite. (October 2017) - Zhao, Zhixi; Wang, Shaofeng; Jia, Yongfeng
Abstract: The sulfide-induced change in arsenic speciation is often coupled to iron geochemical processes, including redox reaction, adsorption/desorption and precipitation/dissolution. Knowledge about how sulfide influenced the coupled geochemistry of iron and arsenic was not explored well up to now. In this work, retention and mobilization of As(III) and As(V) on ferrihydrite in sulfide-rich environment was studied. The initial oxidation states of arsenic and the contact order of sulfide notably influenced arsenic sequestration on ferrihydrite. For As(III) systems, pre-sulfidation of As(III) decreased arsenic sequestration mostly. The arsenic adsorption capacity decreased about 50% in comparison with the system without sulfide addition. For As(V) systems, pre-sulfidation of ferrihydrite decreased 30% sequestration of arsenic on ferrihydrite. Reduction of ferrihydrite by sulfide in As(V) system was higher than that in As(III) system. Geochemical modeling calculations identified formation of thioarsenite in the pre-sulfidation of As(III) system. Formation of arsenic thioanions enhanced As solubility in the pre-sulfidation of As(III) system. The high concentration of sulfide and Fe(II) in pre-sulfidation of ferrihydrite system contributed to saturation of FeS. This supplied new solid phase to immobilize soluble arsenic in aqueous phase. X-ray absorption near edge spectroscopy (XANES) of sulfur K-edge, arsenic K-edge and iron L-edge analysis gave the consistent evidence for the sulfidation reaction of arsenic and ferrihydrite under specific geochemical settings. Graphical abstract: Highlights: Initial oxidation states of arsenic and the contact order of sulfide notably influenced arsenic sequestration on ferrihydrite. Geochemical modeling calculations identified formation of thioarsenite and saturation of FeS. XANES of sulfur K-edge, arsenic K-edge and iron L-edge analysis indicated the sulfidation reaction of arsenic and ferrihydrite.